Effect of CaO/SiO2 and Al2O3 on Viscous Behaviors of the Titanium‐Bearing Blast Furnace Slag. Issue 10 (16th March 2016) - Feng, Cong; Chu, Mansheng; Tang, Jue; Tang, Yating; Liu, Zhenggen
Abstract : In the Blast Furnace (BF) process, the viscous behaviors of molten slags are essential to the efficiency and the productivity of operations. In this work, the effects of CaO/SiO2 and Al2 O3 on the viscosity, activation energy for viscous flow, and break point temperature of titanium‐bearing BF slags are analyzed. To connect the viscosity and the slag structure, Fourier transform infrared spectroscopy (FTIR) is performed on the as‐quenched slags. It is found that the viscosity and the activation energy for viscous flow of slags decrease as the CaO/SiO2 content increases from 1.00 to 1.20 and increase with increasing the Al2 O3 content from 11.00 to 15.00 wt%. As for the break point temperature, it raises when the CaO/SiO2 and the Al2 O3 content increases. FTIR results reveal that the polymerization degree of complex viscous units in the slag decreases as the CaO/SiO2 increases. However, it is opposite when the Al2 O3 content increases. The variation of viscosity and activation energy for viscous flow for the different CaO/SiO2 and Al2 O3 content slags are explained. Abstract : In this study, the viscous behaviors of titanium‐bearing BF slag are investigated by rotating spindle method. Then, the effects of CaO/SiO2 and Al2 O3 on the viscosity, activation energy for viscous flow, and break point temperature of slag are obtained. Besides, the mechanisms on the variation of viscosity and activation energy for viscous flow are acquired by Fourier transform infrared spectroscopy.